Early childhood education and care policies in the U.S. And their impact on family violence. (November 2022) - Maguire-Jack, Kathryn; Hardi, Felicia; Stormer, Bri; Lee, Joyce Y.; Feely, Megan; Rostad, Whitney; Ford, Derek C.; Merrick, Melissa T.; Murphy, Catherine A.; Bart. Klika, J.
Highlights: Studies examining early childhood education policies and family violence are reviewed. Childcare subsidy and HeadStart reduce family violence or its risk factors. Limited research exists on universal pre-k and family violence. Abstract: The current study sought to understand existing literature regarding the relationship between early childhood education and care policies in the U.S. (i.e., childcare subsidies, Head Start, and universal pre-k) and family violence (i.e., child maltreatment and IPV). We examined articles that assessed either of these two family violence outcomes or their related risk factors, including food insecurity, employment, poverty, and parental mental health issues. We conducted a rapid review of literature from the following academic databases: Web of Science, Academic Search Complete, and JSTOR. We examined peer-reviewed journal articles that were published in English between the years of 1996 to 2021. Few studies have investigated the associations between early childhood education and care policies and family violence outcomes. However, of those studies that have examined associations between early childhood education and care policies and family violence outcomes, there is promising evidence to support these policies as a violence prevention strategy.